Use of Electrospun Phenylalanine/Poly-ε-Caprolactone Chiral Hybrid Scaffolds to Promote Endothelial Remodeling - Sun, Benlin; Hou, Lei; Sun, Binbin; Han, Yu; Zou, Yunqing; Huang, Juexin; Zhang, Yanan; Feng, Chuanliang; Dou, Xiaoqiu; Xu, Feng (Frontiers in Bioengineering and Biotechnology, 2021)
The fabrication of tissue-engineered vascular grafts to replace damaged vessels is a promising therapy for cardiovascular diseases. Endothelial remodeling in the lumen of TEVGs is critical for successful revascularization. However, the construction of well-functioning TEVGs remains a fundamental challenge. Herein, chiral hybrid scaffolds were prepared by electrospinning using D/L-phenylalanine based gelators [D(L)PHEG] and poly-ε-caprolactone (PCL). The chirality of scaffolds significantly affected the endothelial remodeling progress of TEVGs. Compared with L-phenylalanine based gelators/poly-ε-caprolactone (L/PCL) and PCL, D-phenylalanine based gelators/poly-ε-caprolactone (D/PCL) scaffolds enhanced cell adhesion, and proliferation and upregulated the expression of fibronectin-1, and vinculin. These results suggests that chiral hybrid scaffolds can promote endothelial remodeling of TEVGs by upregulating adhesion-associated protein levels. This study offers an innovative strategy for endothelial remodeling of TEVGs by fabricating chiral hybrid scaffolds, and provides new insight for the treatment of cardiovascular diseases.